![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)(-13)-4+(-15)-(-36)(2)(+18)+(-12)-6(3)13-|-525|(4)(112-12-13)×24
计算:(1)(-13)-4+(-15)-(-36)(2)(+18)+(-12)-6(3)13-|-525|(4)(112-12-13)×24....
计算:(1)(-13)-4+(-15)-(-36)(2)(+18)+(-12)-6(3)13-|-525|(4)(112-12-13)×24.
展开
1个回答
展开全部
(1)原式=-13-4-15+36=-32+36=4;
(2)原式=18-12-6=0;
(3)原式=13-5
=7
;
(4)原式=24×
-24×
-24×
=2-12-8=-18.
(2)原式=18-12-6=0;
(3)原式=13-5
2 |
5 |
3 |
5 |
(4)原式=24×
1 |
12 |
1 |
2 |
1 |
3 |
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询